IMPLEMENTASI REWARD TERHADAP MINAT BELAJAR MATA PELAJARAN BACA TULIS AL-QUR’AN DI SMP INSAN KAMIL BOGOR - Nida Aghnia Maulida; Ratu Dinny Fauziah (Jurnal Cendekia Ihya, 2025)
Learning in the classroom can determine the success of the learning process. The learner's interest factor can affect the success of the teaching and learning process. Learners who do not have an interest in an object are seen not to respond and will affect the success of the learning process. In implying feelings of pleasure, happiness, making someone more active in increasing and improving the achievements that have been achieved, there needs to be stimulation, one of which is by giving rewards to students. The main purpose of this research is to find out how the implementation of rewards on students' interest in learning the subject of Baca Tulis Al-Qur'an (BTQ). This research approach uses qualitative research. This research was conducted at Insan Kamil Junior High School in Bogor. The subjects of this research are BTQ teachers and class VIII students. Data collection techniques using observation, interview, and documentation methods. From the results of the study that the implementation of rewards on interest in learning the subject of reading and writing the Qur'an at Insan Kamil Junior High School in Bogor has been implemented variably. Rewards are given to students who have performed well when reading yanbu'a, doing assignments correctly on time, mastering the material that has been learned and memorizing the 30th juz Al-Qur'an properly and correctly. Rewards given by teachers are in the form of praise, thanks, giving gifts, making peer tutors and tahfidz certificates from schools. Implementation of the use of The implementation of the use of rewards on learning interest in BTQ subjects makes students more motivated, enthusiastic and enthusiastic during the learning process. Rewards can increase students' interest in learning with an average of 80%, students' attention during learning and increase students' scores. After the reward the teacher sees a change in students on the value of assignments, the value of fluency in reading yanbu'a, memorizing tahfidz and the value of the attitude given. Supporting factors come from the support of teachers, parents and students when after the implementation of rewards, while one of the obstacles is the schedule of learning hours.